Combining in vitro and in ovo assays to screen for anti-cancer and anti-angiogenic effects of the leaf extracts of Mallotus cumingii Müll.Arg. (Euphorbiaceae) - Cruz, Angelo Jud De Paz; Raymundo, Jenina Katrina Galvez; Jacinto, Sonia Donaldo; Tolentino, Jarel Elgin; Ipulan-Colet, Lerrie Ann De Guia (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cancer treatment is often challenging and various interventions may have detrimental effects. Due to this, the development of less harmful alternatives such as herbal medicine is essential. The present study aims to determine the leaf phytoconstituents present and the bioactivities of Mallotus cumingii Müll.Arg against cancer cells through the utilization of MTT assay and anti-angiogenesis through CAM assay. The leaf extracts obtained three fractions namely, methanolic crude (MCME) extracts, hexane extracts (MCHE), and ethyl acetate extracts (MCEA), and was tested on HCT-116 for in vitro cytotoxicity, and blood vessel density and branching through in ovo CAM assay. Phytochemical analysis showed that the M. cumingii fractions contain phenolic compounds, terpenoids, cardiac glycosides, flavonoids, and saponins. For in vitro set-up, MCME of M. cumingii were separated into MCHE and MCEA partitions and were tested against HCT-116 and obtained an IC50 value of < 30 μg/mL, which is deemed active in cytotoxicity. For in ovo set-up, two concentrations of each extract were applied to the duck eggs. Blood vessel density and number of branching points were measured through the ImageJ analysis. All extracts exhibited antiangiogenic activity, either by decreasing blood vessel density or the number of branching points. Overall, the study demonstrates the potential of M. cumingii as a source of therapeutic agents.